Curriculum, Policy, and Politics in English Language Teaching: Comparative Perspectives from Indonesia, Nigeria, and Yemen - Hateenah Ali Sulaiman Yousef; Yeny Prastiwi; Nur Hidayat (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study examines the models, contexts, and ideologies shaping English Language Teaching (ELT) curricula in three developing countries: Indonesia, Nigeria, and Yemen. It focuses on how national priorities, policy orientations, and institutional constraints influence curriculum development and classroom practice. Theoretical framework: The analysis is grounded in Tyler’s (1949) Objectives Model, Taba’s (1962) Grassroots Model, and modern approaches such as Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT). These frameworks are assessed through a critical perspective that views curriculum not only as a pedagogical tool but also as an ideological instrument implicated in debates on linguistic imperialism. Literature review: Previous studies highlight curriculum as both pedagogical and ideological. Tyler’s model, Taba’s grassroots approach, CLT, and TBLT inform debates on policy, context, and linguistic imperialism in developing-country ELT. Methods: A qualitative descriptive approach combined with a critical review of literature was employed. Data included curriculum and policy documents, as well as academic studies published between 2000 and 2024. This triangulated method highlights the interplay between policy design and educational realities. Results: Findings reveal uneven progress. Indonesia shows partial achievement of communicative objectives but struggles with contextual challenges. Nigeria’s curriculum remains dominated by examination-driven practices, limiting communicative competence. Yemen demonstrates stagnation caused by weak governance and insufficient infrastructure. Differences in pedagogy, teaching resources, and assessment underline the gap between intended aims and actual delivery. Implications: Sustainable ELT reform requires systemic teacher training, equitable resource allocation, and contextually relevant policies. Novelty: This comparative study contributes uniquely by integrating literary, pedagogical, and ideological perspectives, offering insights into ELT curricula as both educational frameworks and instruments of political influence.